Functional Transposition of After from a Diachronic Perspective - Kovbasko, Yurii (Baltic Journal of English Language, Literature and Culture, 2022)
The paper aims at tracing the origin of the preposition, adverb, and conjunction after, starting with the first examples registered before 850; distinguishing the primary and transposed categories; and reconstructing the process of functional transposition in general. The analysis is undertaken on the basis of the examples, which have been manually selected from the HCET and the CLMET and have undergone the following PoS tagging, and the statistical data retrieved from the COHA and the BNC. It is proved that after emerges as the preposition and transposes into the adverb and conjunction. The preposition, which predominates throughout Old English, loses its position in favor of the adverb in the second half of the Middle English period. Later, it stabilizes the correlation, which remains more or less consistent up to now. The adverb reaches its peak in Early Modern English, then it starts rapid declension, and now its quantity is close to null. The conjunction, being neglected up to the middle of the Early Modern English period, starts its increase and is at the peak in Present-Day English. It testifies that functional transposition, which is undeservingly disregarded in linguistics, is still remaining in progress for fundamental and newly-coined lexical units.